Some Aspects of Personality of Individual in International Law (Rights of Individual in the International Criminal Court, Rights of Migrants, Refugees, Rights of Women and Children in International Humanitarian Law, Rights of Investors) - NYSSANBEKOVA, Lyazzat; TOKTYBEKOV, Temir; YESSETOVA, Saltanat; ZHANAT, Zhailau (Journal of Advanced Research in Law and Economics, 2017)
The article investigates the controversial issue of international legal personality interpretation. The disparities in understanding the concept of international law subject explain the lack of international legal instruments that could ascertain the exact legal positions of natural persons in question. By a thorough analysis of legal sources, the authors aimed at identifying both general legal parameters of legal personality representation in international law and its individual forms in particular, such as the rights of migrants, refugees, victims of armed conflicts, and investors as economic bloc representatives. The research demonstrates that as opposed to the positions maintained in foreign scientific literature, which tend to treat individuals as subjects of international law, the dominant point of view in the Russian doctrine of international law is the one suggesting that these persons are not subjects of international public law. In the submitted article, the authors entered upon formation of context perception of legal personality and believe that further research might be focused on assessing the degree of compliance of national legislations in coalitions.
Keywords: legal personality of an individual; international law; object humanization; security categories; natural person; criminal court